EXPLORATION OF THE REPRESENTATION OF CULTURAL VALUES IN THE TEXTBOOK NETZWERK B1 DEUTSCH ALS FREMDSPRACHE - Lendo, Sjuul Juliana (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2024)
This study aims to explore cultural values ​​in the Netzwerk B1 textbook, which is widely used in Indonesia. Using a critical social semiotic approach based on Halliday's Systemic Functional Linguistic (SFL) theory, this study examines the semiotic relations between image-text and the cultural meanings contained therein, adopting the semiotic relation model proposed by Xiong and Peng (2021), namely denotational/pedagogic/linguistic relations, denotational/pedagogic relations, and denotational relations. The results show that the Netzwerk B1 textbook provides ample opportunities and space for learners to learn, think, and reflect on German and Indonesian culture, through pedagogical questions in the image-text and in the form of pre-activities or follow-up activities after the image-text is discussed. The implication of this research is that language textbooks should be written and designed with attention to the selection and presentation of cultural materials containing global cultural values ​​and also paying attention to the provision of tasks that can involve learners actively and responsively, whether in the form of hands-on tasks, project-based tasks and problem-based tasks. Thus, learners can have comprehensive cross-cultural knowledge and skills through learning foreign languages, including German.